A randomised controlled trial evaluating family mediated exercise (FAME) therapy following stroke - GALVIN, ROSEMARIE; STOKES, EMMA KATHERINE (BioMed Central, 2008)
Stroke is a leading cause of disability among adults worldwide. Evidence suggests that increased duration of exercise therapy following stroke has a positive impact on functional outcome following stroke. The main objective of this randomised controlled trial is to evaluate the impact of additional family assisted exercise therapy in people with acute stroke.
PUBLISHED
Keywords: Physiotherapy